Rádio-galáxias como possíveis fontes de raios cósmicos ultra-energéticos - Ohtuka, Augusto Kazuyoshi Romasanta (2023)
One of the biggest mysteries in modern physics is revealed by high-energy astrophysics: where the highest-energy cosmic rays come from. It seems that radio galaxies could be the source of the ultra-high cosmic rays (UHECR) that are seen here on Earth. This work examines four prominent radio galaxies in the radio band: NGC 1275, M87, Centaurus A, and Fornax A. Every simulation is injected with ten million particles, taking into account different energy-loss mechanisms and the source’s relative exposure to the observer. Subsequently, the results are contrasted with the flux recorded by the Pierre Auger Observatory. With this method, the most important particle acceleration and energy loss mechanisms in adjacent radio galaxies can be identified. The findings provide a positive outlook on these celestial objects and advance our knowledge of the physics at play as well as the effect these galaxies have on the overall cosmic-ray flux.